2012
DOI: 10.2341/09-228-l
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Potassium Oxalate on Knoop Hardness of Etch-and-Rinse Adhesives

Abstract: Application of potassium oxalate to acid-etched dentin may interfere with the properties of adhesives that are subsequently applied to dentin. SUMMARYThe objective of this study was to determine whether the hardness of etch-and-rinse adhesives may be affected by the pretreatment of acid-etched dentin with potassium oxalate desensitizer. Unerupted human third molars were cut into crown segments by removing the occlusal enamel and roots. The pulp chamber of these crown segments was connected to a syringe barrel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
2
3
1
6
Order By: Relevance
“…Because the inclusion of solvent and hydrophilic compounds in the two‐step conventional adhesive should theoretically result in low bond strength (Paul, Leach, Rueggeberg, & Pashley, ), this may have occurred by incomplete solvent evaporation in the SB group, which would weaken the bonding (Hashimoto et al, ). The lack of a statistically significant difference between these types of adhesive systems corroborates the findings of another study (Silva et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Because the inclusion of solvent and hydrophilic compounds in the two‐step conventional adhesive should theoretically result in low bond strength (Paul, Leach, Rueggeberg, & Pashley, ), this may have occurred by incomplete solvent evaporation in the SB group, which would weaken the bonding (Hashimoto et al, ). The lack of a statistically significant difference between these types of adhesive systems corroborates the findings of another study (Silva et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…(Paul, Leach, Rueggeberg, & Pashley, 1999), this may have occurred by incomplete solvent evaporation in the SB group, which would weaken the bonding (Hashimoto et al, 2006). The lack of a statistically significant difference between these types of adhesive systems corroborates the findings of another study (Silva et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…They used the microtensile method in the laboratory and showed that, despite oxalate desensitizer being shown to contribute to the reduction of resin-dentin bond degradation over time, it compromised the baseline bond strength to the teeth that received potassium oxalate after acid etching. After 2 years, they also showed that the potassium oxalate may adversely affect the baseline hardness of etch-and-rinse adhesives [34]. Therefore, in accordance with these previous studies [21,[29][30][31][32][33][34], it can speculate that crystal precipitation on the etched dentin surface impaired the adequate hybrid layer formation.…”
Section: Discussionmentioning
confidence: 61%
“…After 2 years, they also showed that the potassium oxalate may adversely affect the baseline hardness of etch-and-rinse adhesives [34]. Therefore, in accordance with these previous studies [21,[29][30][31][32][33][34], it can speculate that crystal precipitation on the etched dentin surface impaired the adequate hybrid layer formation.…”
Section: Discussionmentioning
confidence: 61%
“…Desde que a mensuração da dureza foi aceita como um bom indicador do grau de polimerização das resinas compostas, têm sido realizados estudos que utilizam ensaios de dureza para avaliar esta propriedade nos sistemas adesivos (Hass et al, 2011;Silva et al, 2012 (Shimada et al, 2003;Senawongse et al, 2004).…”
Section: Revisão Da Literaturaunclassified